Perubahan Model Bisnis Media Massa Dalam Era Digital: Dampaknya Terhadap Kualitas Jurnalisme Modern Di Sumatera Ekspres - Dwi Saputra; Sumaina Duku; Jufrizal Jufrizal (CV. ITTC INDONESIA, 2025)
The development of communication and information technology has threatened the print media industry. The most obvious threat is the reduction in print media readers who have switched to online media. Therefore, changes are needed to maintain the current print media industry, one of which is through media convergence. This study aims to determine how changes in the mass media business model in the digital era affect the quality of modern journalism at Sumatera Ekspres and the journalistic convergence model applied in the process towards media change carried out by Sumatera Ekspres. In this study, the researcher used qualitative research methods and a case study approach. The results of the study show that Sumatera Ekspres carried out a media convergence transformation by changing news platforms, improving quality, and utilizing social media. Sumatera Ekspres uses the journalistic convergence model according to Grant, namely newsroom convergence, newsgathering convergence and content convergence. In its application, Sumatera Ekspres has carried out newsroom convergence to the maximum because it uses rooms that have been combined in producing news on each platform. Newsgathering convergence where in this model reporters are required to be able to work multitasking and content convergence is a convergence model that provides content in multimedia form with a combination of images, videos, writing, andpodcasts.